Dampak Kualitas Laporan Keuangan Perusahaan Badan Usaha Milik Negara Terhadap Efisiensi Investasi - Novita Sherla Hariyanto; Tarsisius Renald Suganda; Putu Indrajaya Lembut (Jurnal Akuntansi)
This study aims to investigate the effects of financial statements’ quality towards over/under investment, the internal controls’ implementation towards over/under investment, and moreover the internal control as a moderating variable to strengthen the financial statements’ quality to over/under investment on state-owned listed companies in Indonesia Stock Exchange and state-owned non-listed companies as well. The data analysis techniques namely logistic regression analysis is used to measure the research problems. There are 96 listed and non-listed state-owned companies (not including financial services and insurance) used as research sample during period from 2015 to 2018. The findings of this study reject first and third hypotheses stating that the financial statements’ quality does not affect over/under investment and moreover, internal control as a moderating variable could not strengthen the effect of financial statements’ quality towards over/under investment. However, on the other hand, the second hypothesis in this study is accepted proofing that the implementation of internal control has positive effect on over/under investment.